DRIVING PERFORMANCE OF SMES: SYSTEMATIC REVIEW ON THE EFFECT OF ORGANIZATIONAL CULTURE ON THE IMPLEMENTATION OF GREEN MARKETING STRATEGIES - Abdullah, Al Farsi Ahmed Hamdan; Jamaludin, Hamiza binti (Veredas do Direito, 2026)
Small and Medium Enterprises (SMEs) are key stakeholders in broadening economic diversification, especially in developing countries such as Oman. As competition stiffens and environmental concerns grow, green marketing has become a go-to strategy for SMEs aiming to improve sustainability and performance. But real-world data shows that adopting green marketing doesn't always lead to better outcomes. This suggests that internal organisational conditions might be a deciding factor. Most current research focuses on the direct link between green marketing and performance, often missing the critical roles of culture and management. This systematic review addresses that gap by exploring how organisational culture influences the relationship between green marketing and SME performance. Using the PRISMA framework, we searched eight academic databases, including Scopus and Web of Science. The search covered publications from 2010 to 2025, initially yielding 4,842 records for screening. Following rigorous multi-stage screening, 104 studies met the inclusion criteria for qualitative synthesis. The findings demonstrate that a green organisational culture—characterised by shared environmental values, employee engagement, and innovation orientation—acts as a key mechanism translating green marketing initiatives into tangible economic and environmental outcomes. The study concludes that effective green marketing implementation is fundamentally a cultural process, offering important implications for SME practitioners and policymakers seeking sustainable competitive advantage.